(untitled) (Jurnal Sosial Ekonomi Pertanian, 2020)
This study aims to determine the cost, revenue, profit, and R / C ratio, internal and external factors that influence the development of banana chips agroindustry, an alternative strategy that can be applied in the development of banana chips agroindustry in Pontianak City. The type of research used in this study is the case study method. Data collected includes primary data and secondary data. The respondent’s withdrawal in this study was purposive sampling, which was determining the sample with consideration of certain criteria which looked at being able to provide maximum data, then the respondents who were taken were banana chips entrepreneurs and as supporting respondents namely one person. Agriculture Service and one person from academia. The results showed that the total costs incurred by banana chips entrepreneurs in one month of the production process amounted to Rp. 22,030,029, revenues amounting to Rp. 46,090,000, the profits amounting to Rp. 24,059,971 and added value of Rp. 15,114 / kg of raw materials. R / C ratio of 2.09, which means that every expenditure of Rp. 1.00 banana chips businessmen get a profit of Rp. 1.09 which means that the business of banana chips is worth trying. The development strategy that can be done by banana chips entrepreneurs is an aggressive strategy with more focus on the strategy of SO (Strength-Opportunities), namely by using the power to take advantage of the opportunities that exist. SO (Strength-Opportunities) strategies include: (a) Increasing economic production capacity to meet demand, (b) Use of Technology, (c) Enlarging market share, (d) Maintaining the quality of banana chips products, and (e) Making product innovations. This study aims to determine the cost, revenue, profit, and R / C ratio, internal and external factors that influence the development of banana chips agroindustry, an alternative strategy that can be applied in the development of banana chips agroindustry in Pontianak City. The type of research used in this study is the case study method. Data collected includes primary data and secondary data. The respondent’s withdrawal in this study was purposive sampling, which was determining the sample with consideration of certain criteria which looked at being able to provide maximum data, then the respondents who were taken were banana chips entrepreneurs and as supporting respondents namely one person. Agriculture Service and one person from academia. The results showed that the total costs incurred by banana chips entrepreneurs in one month of the production process amounted to Rp. 22,030,029, revenues amounting to Rp. 46,090,000, the profits amounting to Rp. 24,059,971 and added value of Rp. 15,114 / kg of raw materials. R / C ratio of 2.09, which means that every expenditure of Rp. 1.00 banana chips businessmen get a profit of Rp. 1.09 which means that the business of banana chips is worth trying. The development strategy that can be done by banana chips entrepreneurs is an aggressive strategy with more focus on the strategy of SO (Strength-Opportunities), namely by using the power to take advantage of the opportunities that exist. SO (Strength-Opportunities) strategies include: (a) Increasing economic production capacity to meet demand, (b) Use of Technology, (c) Enlarging market share, (d) Maintaining the quality of banana chips products, and (e) Making product innovations.